Environmental and safety aspects of renewable materials and energy sources - Ladomerský, Juraj (Advanced materials research, 2014)
This special topic volume tends to present leading publications dealing with the Environmental and Safety Aspects of Renewable Materials and Energy Sources. The aims and scope are divided into four main areas: Chapter 1. Environmental aspects of selected renewable sources, Chapter 2. Fire safety aspects of selected renewable sources, Chapter 3. Occupational safety and health aspects of selected renewable sources, Chapter 4. Other safety aspects of selected renewable sources.